Anticomplement triterpenoids from the roots of Ilex asprella. Issue 4 (15th February 2017) - Wen, Quan; Lu, Yan; Chao, Zhi; Chen, Dao-feng
Graphical abstract: Highlights: Five new ursane and oleanane triterpenoids were isolated from the roots of Ilex asprella. Several triterpenoids were found to show anticomplement activity. The targets of the bioactive triterpenoids in complement activation cascade were identified. Abstract: Five new (1 –5 ) and twenty-eight known (6 –33 ) triterpenoids were isolated from the roots of Ilex asprella . The structures of the new compounds were elucidated by the detailed spectral analysis. The ursane and oleanane triterpenoids were found to show anticomplement activity with some structure-activity relationships. Several triterpenoids (1 –3, 6 –7) exhibited potent anticomplement activity with the CH50 and AP50 values of 0.058–0.131 mg/mL and 0.080–0.444 mg/mL, respectively. It was found that caffeoyl group could enhance activity remarkably, followed by coumaroyl and feruloyl group. The 28-carboxyl group was also important to anticomplement activity for the triterpenoids. However, the triterpenoids with lactone ring (4, 9 –14) exhibited weak activity and triterpenoid glycosides (5, 23 –33) showed no inhibition. The targets of several bioactive triterpenoids in complement activation cascade were identified as well.